Realist evaluation in practice : health and social work - Kazi, Mansoor A. F. (Online access: SAGE SAGE Research Methods Core., 2003)
Realist Evaluation in Practice outlines the new, emerging realist paradigm in evaluation research and applies it to practice in human services. There are, to date very few published examples where realist evaluation has been put into practice and here the author contributes to the development of this paradigm in practice and provides lively examples of realist evaluations in the human services.